SEJARAH PERTUMBUHAN DAN PERKEMBANGAN ILMU AKHLAK - Muhammad Hasbi Nabil; Jidan Muzadi; Maftuh Ajmain (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
Moral science is one of the branches of science that studies morality and ethics in human life. The history of the growth and development of moral science can be seen from several periods, namely the classical period, the medieval period, the modern period, and the contemporary period. In each period, moral science underwent significant development, both in terms of concepts, theories, and applications. This article also discusses important figures who played a role in the development of moral science, such as Imam Ghazali, and Ibn Khaldun. By understanding the history of the growth and development of moral science, it is hoped that it can provide broader insights into the importance of moral science in human life.